The Battle of the Skamander - Kącka, Eliza (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The article offers a reconstruction of the text-based fight between Adolf Nowaczyński and Antoni Słonimski. It was not, as it is argued here, only a contest of styles and temperaments – though this exchange proved one of the most impressive, powerful, and dramatic polemics of that time in terms of articulation. However, it stemmed from a long history of tumultuous contacts which offered an amplified view of the problems of identity (Jewishness), politics, and community. A comprehensive view of the combat between Nowaczyński and Słonimski requires both an analysis of the rhetorics of the texts and an investigation into the context and dynamics of publication.